HUBUNGAN E-WOM DAN E-LOYALTY DENGAN REPURCHASE PADA KONSUMEN SHOPEE - Afifah Nuraini; Widarto Rachbini (CV SWA Anugerah, 2024)
This study aims to analyze the relationship between Electronic Word of Mouth (E-WOM) and Electronic Loyalty (E-Loyalty) on repurchase decisions for Shopee e-commerce platform consumers. E-WOM is a form of communication between consumers digitally that influences perceptions and purchasing preferences, while E-Loyalty reflects the level of consumer loyalty to the e-commerce platform. Repurchase is an important indicator to assess the success of the platform in retaining consumers. A quantitative approach was used in this study, with a survey method to collect data from respondents who are active Shopee users. The data was analyzed using multiple linear regression to test the simultaneous and partial effects of E-WOM and E-Loyalty on repurchase. The results showed that E-WOM and E-Loyalty simultaneously have a significant influence on consumer repurchase decisions at Shopee, with an R Square value of 34.1%, which indicates that the two independent variables explain most of the variation in repurchase decisions. Partially, E-Loyalty has a more dominant influence than E-WOM on repurchase decisions. This research implies that Shopee needs to improve digital communication strategies that encourage positive E-WOM, while strengthening consumer loyalty by providing a consistent and satisfying shopping experience. Thus, the level of repurchase